Economic Analysis of Initial Returns: The Impact of Stock Price, Offering Value, and Firm Age at Bank BCA (2020–2023) - Tarigan, Agnes Silvia Br; Barasa, Putriani; Sitepu, Calvin Frenares; Najmi, Hendra; Dewi, Sri Puspa (International Journal of Economics Development Research (IJEDR), 2025)
Banking stocks have consistently delivered substantial profits for investors, particularly throughout 2023. According to data from the Financial Services Authority (OJK) in 2020, Indonesian banking assets reached IDR 9,333 trillion, equivalent to 59.5% of the country’s Gross Domestic Product (GDP), highlighting the sector's significant role in national economic growth. Furthermore, Kontan (2023) reported that Bank Central Asia (BCA) was among the top-performing banking issuers, achieving a total stock return of 12.60% in 2023. This study aims to analyze the economic and financial factors—specifically the quantity of stock prices, stock offering values, and company age—that influence initial stock returns. Using a multiple linear regression model, the findings reveal that the quantity of stock prices has a significant negative effect on initial returns. In contrast, the stock offering value and the age of the company do not exhibit a significant individual impact. However, collectively, these variables—representing key economic indicators—have a significant joint effect on the initial return of Bank BCA. The study contributes to the broader understanding of how financial metrics and firm characteristics affect investment performance in the banking sector, especially in emerging markets like Indonesia.